APPLICATION OF NEURAL NETWORK TECHNOLOGIES FOR MANAGEMENT DEVELOPMENT OF SYSTEMS - A. L. Lisovsky (Стратегические решения и риск-менеджмент)
Work is devoted to application of neural network technologies for management development of systems. In article the analysis of efficiency of introduction of neural network technologies is carried out to business processes of three Russian companies and the positive effect locates when using neural networks in several parameters.The case analysis is added with the analysis of economic feasibility of introduction of neural networks by means of an assessment of studied indicators, an assessment of satisfaction of clients, control of the personnel, an assessment of efficiency of each employee. Recommendations about application of neural networks in the organization are made.In article it is shown that in spite of the fact that many actions necessary for introduction of system, are costly and long-term, they will positively affect company activity.